Getting in the game : Title IX and the women's sports revolution - Brake, Deborah L. (New York : New York University Press, 2016)
In this legal analysis of Title IX, the book assesses the statute's successes and failures, using a feminist theory lens to understand, defend, and critique the law. While the statute has created tremendous gains for female athletes, not only raising the visibility and cultural acceptance of women in sports, but also creating social bonds for women, positive body images, and leadership roles, the disparities in funding between men's and women's sports have remained remarkably resilient. At the same time, female athletes continue to receive less prestige and support than their male counterparts, which in turn filters into the arena of professional sports. The book provides a richer understanding and appreciation of what Title IX has accomplished, while taking a critical look at the places where the law has fallen short.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: United States; Sex discrimination in sports -- Law and legislation -- United States; Women athletes -- Legal status, laws, etc. -- United States; Law; United States of America, USA; Gender studies: women & girls; Sociology: sport & leisure; Jurisprudence & general issues; Law & society, gender issues